2016
DOI: 10.4194/1303-2712-v16_3_20
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fuel price increases have been identified as a major factor explaining the low economic performance of fishing fleets. Fishers have reacted by reducing costs and increasing fuel efficiency of their vessels when possible, and by reducing the days spent at sea or ceasing activity. However, fuel prices explain only part of the story. We analyzed the evolution of fuel prices, fish prices, fishing activity and productivity over a 14 year period (2000-13) for the Catalan fleet (Spanish Mediterranean). Most fish pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The decrease in production might be further aggravated by environmental factors (i.e., weather conditions), social (i.e., conflict with other users), and economic (i.e., increased fuel price) that the fishers encountered. Guillen and Maynou (2016) stated that the main reasons for the decrease in economic performance and fishing activity of fishers are increases in fuel prices together with low prices of fish and low fish productivity. The author also further concluded that fuel cost can represent 50% of the total fishing cost, so fishing performance is very dependent on the fuel price.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in production might be further aggravated by environmental factors (i.e., weather conditions), social (i.e., conflict with other users), and economic (i.e., increased fuel price) that the fishers encountered. Guillen and Maynou (2016) stated that the main reasons for the decrease in economic performance and fishing activity of fishers are increases in fuel prices together with low prices of fish and low fish productivity. The author also further concluded that fuel cost can represent 50% of the total fishing cost, so fishing performance is very dependent on the fuel price.…”
Section: Discussionmentioning
confidence: 99%
“…High fuel prices and the consequent increase in fuel costs often lead to a reduction in fishing effort and changes in fishing strategies [3][4][5][6][7][8], aiming at reducing fuel consumption and costs. This implies that the weight of landings in 2022 could well be below the average annual quantities landed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, fuel costs represented 21% of the operational costs in the EU fishing fleet [2]. Hence, the economic performance of the fishing sector is very sensitive to fuel prices [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, little is known about the impact of a large reduction in fishing effort (either through fewer trawlers or fewer fishing days) on fish markets as well as on the economic situation of fisheries (Guillen and Maynou, 2016;Sabatella et al, 2017). In this paper, we focus on this issue using the following natural experiment.…”
Section: Introductionmentioning
confidence: 99%